DEVELOPMENT AND VALIDATION OF STABILITY INDICATING RP-HPLC METHOD FOR THE SIMULTANEOUS ESTIMATION OF ACLIDINIUM BROMIDE AND FORMOTEROL FUMARATE IN BULK AND INHALER FORMULATION - LAKSHMI, A. JAYA; ABHISHEK, K.; PRIYANKA, Y. LEELA; BALAJI, P. V.; ASHRITHA, N. (International Journal of Current Pharmaceutical Research, 2022)
Objective: To develop a simple, accurate, precise, rapid and sensitive method for the simultaneous estimation of Formoterol fumarate and Aclidinium bromide in pharmaceutical dosage form. Methods: The chromatogram was run through Ascentis C18 150 x 4.6 mm, 5µ. Mobile phase containing Water: Acetonitrile taken in the ratio 60:40 was pumped through the column at a flow rate of 1.0 ml/min. The temperature was maintained at 30 °C. The optimized wavelength selected was 220 nm. Results: The retention times of Formoterol fumarate and Aclidinium bromide were found to be 2.953 min and 2.364 min. %RSD of the Aclidinium bromide and Formoterol fumarate was found to be 0.6 and 0.9, respectively. %Recovery was obtained as 99.81 % and 100.20% for Aclidinium bromide and Formoterol fumarate, respectively. LOD, LOQ values obtained from the Signal-to-noise ratio of Aclidinium bromide and Formoterol fumarate were 0.84 µg/ml, 2.56 µg/ml and 0.01 µg/ml, 0.03µg/ml respectively. Regression equation of Formoterol fumarate is y =9023x+268.67, and y = 4661.2x+1941.9 of Aclidinium bromide. Retention times were decreased and that run time was decreased, so the method developed was simple, rapid, sensitive and economical that can be adopted in regular quality control tests in Industries. Conclusion: Developed and Validated Formoterol fumarate and Aclidinium bromide in pharmaceutical dosage form by using RP-HPLC method.